Ginseng roots : a memoir - Thompson, Craig, 1975- (Pantheon Books, 2025)
"From the celebrated author of Blankets and Habibi comes a long-awaited return to the graphic memoir form. Ginseng Roots follows Craig Thompson and his siblings-who spent the summers of their youth weeding and harvesting rows of coveted American ginseng on rural Wisconsin farms for one dollar an hour-and interweaves this lost youth with the three-hundred-year history of the global ginseng trade and the many lives it has tied together. Stretching from Marathon, Wisconsin, to northeast China, Ginseng Roots charts the rise of industrial agriculture, the decline of American labor, and the search for a sense of home in a rapidly changing world"--